The Acculturation of Malay-Islamic Elements in the Dabus Dance Ritual in the Malay Community of Perak, Malaysia - Chan, Abdul Hamid; Saearani, Muhammad Fazli Taib; Alfarisi, Salman (Department of Drama, Dance and Music, FBS, Universitas Negeri Semarang, 2024)
The main objective of this study is to examine the Islamic and Malay elements that are acculturated in the Dabus dance ritual of Perak, Malaysia. The focused group of this study is the Dabus of Tanjung Bidara village, estimated to have been established since the 1818s. However, throughout that time, the perception of the Malay community has not been strong yet, specifically regarding the ritual relationship of the Dabus dance with Islamic values. In fact, not infrequently, Dabus dance rituals are seen as contradicting the values of Islam itself. It is even seen over as skewed by some of the Malay community. However, in terms of history, meaning, practice, and ritual function, the Dabus dance itself cannot be separated from Islam. The study was designed as a field study. The data collected is qualitative and analysed critically using ritual theory, cultural symbols, and acculturation. Data was collected through interviews, field observations, and documents. Other data sources include a review of text, photos, videos, and relevant articles. The findings show that 1) the process of Malay-Islamic acculturation in Dabus dance rituals has been since the arrival of Dabus dance in the Malay peninsula and continues until now; 2) one of the most significant Islamic-Malay acculturation methods and strategies is the reinvention of the Dabus dance over time; 3) Islamic-Malay acculturation includes not only physical forms (forms, structures, and ritual elements) but also non-physical aspects (doa, zikir, selawat, berzanji, belief).